Shooting Accuracy Survey of SKIP PGRI Sumenep Handball’s Player - Prasetyo, Dyas Andry; Nordiansyah, Shally (Journal of Physical Education Health and Sport, 2020)
The objective of this study is to determine the level of shooting accuracy in handball game. The method of this research is survey research type with a quantitative descriptive approach. The research sample consisted of 15 people who were determined by using purposive sampling technique. The data collection was obtained by doing a shooting test towards the goal with a target point. The instrument used was in a form of testing the accuracy of shooting in handball game. The data analysis technique applied was the percentage formula with the help of the Software Statistical Product and Service Solution (SPSS) version 18.0 application. The results of the data analysis show that most of the male handball players’ shooting accuracy in STKIP PGRI Sumenepis categorized‘good’ with a percentage of 86.67% and the remaining as much as 13.33% have shooting accuracy level in ‘moderate’ category. The conclusion of this research is that the male handball players of STKIP PGRI Sumenephave good shooting accuracy.